CPC-109 Pharmacy Intravenous Iron Protocol in a Central Hospital. (12th March 2013) - Amaral, J; Parola, A; Farinha, H; Falcao, F
Abstract : Background: Iron deficiency anaemia (IDA) is a common condition. The pharmacy intravenous iron protocol (100 mg/5 ml iron sucrose vials) includes assessment of patient analytical data, dose calculation, schedule and information about iron administration intended to prevent adverse reactions. Purpose: To assess the use of intravenous iron in hospitalised patients being treated by the pharmacy protocol. Materials and Methods: An eight-month retrospective, observational study (January to August 2012). Hospitalized patients treated with pharmacist-managed intravenous iron were selected. Demography, main diagnosis, comorbidities, basic data, dosage suggestions and haemoglobin and haematocrit values were collected from electronic clinical files and pharmacotherapeutic profiles. Results: A total of 35 patients (19 male) were included. Mean age was 75.9 years (range 43–94). 9 (25.7%) patients were admitted for surgery and 26 (74.3%) for a variety of medical conditions. 20 patients (57.1%) were treated without complete investigation of the anaemia. The most frequent intravenous iron dosage was 200 mg 3x week. 27 (77.1%) patients had increased haemoglobin and haematocrit values after an average of 10.3 days (range 3–20) of intravenous iron replacement treatment. The mean increase in haemoglobin concentration was 2.5 g/dl (range 0.2–6.6). Only 9 patients (25.7%) achieved the haemoglobin target during admission. The majority of patients were discharge before achieving the target haemoglobin. No adverse reactions were reported to the pharmacist. Conclusions: As stated in the literature, a large proportion of patients in our study were not confirmed to be iron deficient. Pharmacist should advise physicians about the importance of a complete IDA study before starting this therapy. The information about iron administration and a test dose in the pharmacy protocol seem to be useful in preventing adverse reactions. No conflict of interest.